Figurative Language Used In Genshin Impact’s and Honkai: Star Rail’s Special Program Videos - Euginea Kezia Lie; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study aimed to identify various types of figurative language used in the video advertisements for two games, Genshin Impact and Honkai: Star Rail. Following Harris's (2018) theory on rhetorical devices, particularly figurative language, the researchers analyzed the utterances in these videos. According to Harris (2018), there are 11 types of figurative language namely: simile, analogy, metaphor, catachresis, metonymy, synecdoche, personification, allusion, eponym, apostrophe, and transferred epithet. Using qualitative research methods, the researchers collected and analyzed the data. The results indicated that the types of figurative language found in Genshin Impact were simile, analogy, metaphor, metonymy, synecdoche, personification, and allusion whereas simile, analogy, metaphor, metonymy, personification, and allusion were found in Honkai: Star Rail. Synecdoche, personification, and the combination of metaphor and synecdoche were absent in Honkai: Star Rail. The possible reasons for the differences might probably because of the differences in the game’s themes and the amount of information.